2021
DOI: 10.3390/rel12060423
|View full text |Cite
|
Sign up to set email alerts
|

Þingeyrar Abbey in Northern Iceland: A Benedictine Powerhouse of Cultural Heritage

Abstract: Þingeyrar Abbey was founded in 1133 and dissolved in the wake of the Lutheran Reformation (1550), to virtually disappear with time from the face of the earth. Although highly promising archeological excavations are under way, our material points of access to this important monastic foundation are still only a handful of medieval artifacts. However, throughout its medieval existence Þingeyrar Abbey was an inordinately large producer of Latin and Icelandic literature. We have the names of monastic authors, poets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The reproduction of a readable text of the Regula Benedicti and the Decreta Lanfranci-before the mid-thirteenth century the only complement to the rule that seems to have passed between houses speaks of a pattern of monastic education and formation in a Nordic community which counterparts in other northern European regions would have known well. The trace of monastic-Benedictine, Cistercian-attributes in the saga portraits produced at Þingeyrar at this same time, in the years either side of 1200, might be taken as another signal of a quickening of a distinctively monastic outlook (Jensson 2021).…”
Section: The Deepening Of Monastic Identitymentioning
confidence: 92%
See 2 more Smart Citations
“…The reproduction of a readable text of the Regula Benedicti and the Decreta Lanfranci-before the mid-thirteenth century the only complement to the rule that seems to have passed between houses speaks of a pattern of monastic education and formation in a Nordic community which counterparts in other northern European regions would have known well. The trace of monastic-Benedictine, Cistercian-attributes in the saga portraits produced at Þingeyrar at this same time, in the years either side of 1200, might be taken as another signal of a quickening of a distinctively monastic outlook (Jensson 2021).…”
Section: The Deepening Of Monastic Identitymentioning
confidence: 92%
“…Excavations have indicated that the effects of its enterprise on life and livelihood would have been visible even to the generation that saw them arrive (Borgehammar and Wienberg 2012;Riddell et al 2018). In fact, the true scale of the monastic presence is still coming into focus as both manuscript and material remains are subject to fresh analysis (Borgehammar and Wienberg 2012;Kristjánsdóttir 2014aKristjánsdóttir , 2015aKristjánsdóttir , 2015bKristjánsdóttir , 2017Riddell et al 2018;Ommundsen 2008;Gullick 2013;Jensson 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It had a supremely literate population, even according to Icelandic standards. When dissolved as late as 1551, during the Reformation in Iceland (Kristjánsdóttir 2021), the Abbey had been in operation for 418 years, and would through its extraordinarily rich literary production leave an indelible mark on Northern-European cultural heritage (Jensson 2021c). But even after Þingeyrar Abbey was dissolved in the middle of the 16th century, its successor institution, still referred to as Þingeyrar Cloister, was operated for another 261 years as a crown ecclesiastical and agricultural estate.…”
Section: The Long Life Of þIngeyrar Abbey and Cloistermentioning
confidence: 99%
“…This demonstrates well the functionality of the vernacular as a business language in Iceland, but it obviously does not indicate any rule against using Latin in charters, or that the Thingeyrenses weren't able to use Latin. As we have seen, their library was full of Latin books, and besides, the monks of Þingeyrar Abbey were by far the most prolific authors of Latin texts in Iceland (Jensson 2017(Jensson , 2021c, where charters in Latin are well attested and were often used.…”
Section: The Archive Of þIngeyrarmentioning
confidence: 99%